Long-term personal air pollution exposure and risk for acute exacerbation of idiopathic pulmonary fibrosis - Ioannis Tomos; Konstantina Dimakopoulou; Effrosyni D. Manali; Spyros A. Papiris; Anna Karakatsani (BMC, 2021)
Abstract Background Urban air pollution is involved in the progress of idiopathic pulmonary fibrosis (IPF). Its potential role on the devastating event of Acute Exacerbation of IPF (AE-IPF) needs to be clarified. This study examined the association between long-term personal air pollution exposure and AE- IPF risk taking into consideration inflammatory mediators and telomere length (TL). Methods All consecutive IPF-patients referred to our Hospital from October 2013-June 2019 were included. AE-IPF events were recorded and inflammatory mediators and TL measured. Long-term personal air pollution exposures were assigned to each patient retrospectively, for O3, NO2, PM2.5 [and PM10, based on geo-coded residential addresses. Logistic regression models assessed the association of air pollutants' levels with AE-IPF and inflammatory mediators adjusting for potential confounders. Results 118 IPF patients (mean age 72 ± 8.3 years) were analyzed. We detected positive significant associations between AE-IPF and a 10 μg/m3 increase in previous-year mean level of NO2 (OR = 1.52, 95%CI:1.15-2.0, p = 0.003), PM2.5 (OR = 2.21, 95%CI:1.16-4.20, p = 0.016) and PM10 (OR = 2.18, 95%CI:1.15-4.15, p = 0.017) independent of age, gender, smoking, lung function and antifibrotic treatment. Introduction of TL in all models of a subgroup of 36 patients did not change the direction of the observed associations. Finally, O3 was positively associated with %change of IL-4 (p = 0.014) whilst PM2.5, PM10 and NO2 were inversely associated with %changes of IL-4 (p = 0.003, p = 0.003, p = 0.032) and osteopontin (p = 0.013, p = 0.013, p = 0.085) respectively. Conclusions Long-term personal exposure to increased concentrations of air pollutants is an independent risk factor of AE-IPF. Inflammatory mediators implicated in lung repair mechanisms are involved.